CHARACTERISATION OF PRODUCTIVITY LIMITATION OF SALT‐AFFECTED LANDS IN DIFFERENT CLIMATIC REGIONS OF EUROPE USING REMOTE SENSING DERIVED PRODUCTIVITY INDICATORS. (20th September 2011) - Ivits, E.; Cherlet, M.; Tóth, T.; Lewińska, K. E.; Tóth, G.
ABSTRACT Soil salinity is a global issue and one of the major causes of land degradation. The large scale monitoring of salt‐affected areas is therefore very important to shed light on necessary rehabilitation measures and to avoid further land degradation. We address the productivity limitation of salt‐affected soils across the European continent by the usage of soil maps and high temporal resolution time series of satellite images derived from the SPOT vegetation sensor. Using the yearly dynamism of the vegetation signal derived from the Normalised Difference Vegetation Index, we decomposed the spectral curve into its base fraction and seasonal dynamism fractions next to an index approximating gross primary productivity. We observe gross primary productivity, base fraction and seasonal dynamism productivity differences of saline, sodic and not salt‐affected soils under croplands and grasslands in four major climatic zones of the European continent. Analysis of variance models and post hoc tests of mean productivity values indicate significant productivity differences between the observed salt‐affected and salt free areas, between management levels of soils as well as between the saline and sodic character of the land. The analysis gives insight into the limiting effect of climate in relation to the productivity of salt‐affected soils. The proposed indicators are applicable on the global level, are objective and readily repeatable with yearly updates, thus, might contribute to the global operational monitoring and assessment of degraded lands. Copyright © 2011 John Wiley & Sons, Ltd.